The Strategy of Political Parties in Wining Legislative Elections in Indonesia: Studies in Dharmasraya District - Atri Waldi; Miyato Miyato; Maria Montessori; Nazirwan Nazirwan; Risnaldi Ibrahim; Sabiruddin Sabiruddin (International Journal of Multidisciplinary Research of Higher Education, 2018)
Political parties are political participation in constitutional democratic in an effort to realize the national ideals of Indonesian people. In a democratic party, electoral activities are an arena to express people's freedom in choosing and selecting their leaders. Therefore political parties as political machinery must have the best strategy in order to understand people's tastes to achieve party victory through legislative elections. This study aims to find out how the strategy of political parties in winning elections for legislative members in Dharmasraya Regency, West Sumatra Province. The study used a qualitative method with a case study approach (case research design study). All data taken through in-depth interviews to ten informants consisting of administrators of political parties, legislative members, political observers, and the public. The data obtained then analyzed thematically by means of being collected, reduced, presented and closed with conclusions. The results of the study found that there are four strategies carried out by political parties in winning legislative members at the time of the election, namely; first, utilizing the influence of party leaders, secondly, disseminating legislative candidates through print and electronic media, thirdly, procuring self-sufficiency by legislative candidates and fourth, direct socialization of legislative candidates to the public.